2004
DOI: 10.1161/01.res.0000115557.25127.8d
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Induces Oxidative Stress and Endothelial Dysfunction by Overexpression of the Angiotensin II Type 1 Receptor

Abstract: Abstract-Angiotensin II type 1 (AT 1 ) receptor activation as well as proinflammatory cytokines such as interleukin-6 (IL-6) are involved in the development and progression of atherosclerosis. The detailed underlying mechanisms including interactions between inflammatory agonists and the renin-angiotensin system are poorly understood. Stimulation of cultured rat aortic vascular smooth muscle cells (VSMCs) with IL-6 led to upregulation of AT 1 receptor mRNA and protein expression, as assessed by Northern and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
300
1
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(320 citation statements)
references
References 61 publications
12
300
1
7
Order By: Relevance
“…Indeed, the expression level of the AT 1 receptor in vascular cells is upregulated by low-density lipoprotein cholesterol, 13 insulin, 14 glucose, 15 progesterone 16 and inflammatory cytokines, such as interleukin-1a or interleukin-6. 17,18 Analyses of the binding affinity of olmesartan for mutant AT 1 receptors as well as molecular modeling analyses indicated that the ternary interactions between the hydroxyl group and Tyr 113 and between the carboxyl group and Lys 199 and His 256 are critical to the inverse agonist properties of olmesartan, but that the interaction between the tetrazole group and Gln 257 is dispensable. 9 Interestingly, differential interactions between valsartan and Ser 105 , and between Ser 109 and Lys 199 , are crucial for producing inverse agonism.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the expression level of the AT 1 receptor in vascular cells is upregulated by low-density lipoprotein cholesterol, 13 insulin, 14 glucose, 15 progesterone 16 and inflammatory cytokines, such as interleukin-1a or interleukin-6. 17,18 Analyses of the binding affinity of olmesartan for mutant AT 1 receptors as well as molecular modeling analyses indicated that the ternary interactions between the hydroxyl group and Tyr 113 and between the carboxyl group and Lys 199 and His 256 are critical to the inverse agonist properties of olmesartan, but that the interaction between the tetrazole group and Gln 257 is dispensable. 9 Interestingly, differential interactions between valsartan and Ser 105 , and between Ser 109 and Lys 199 , are crucial for producing inverse agonism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a relation between the pro-inflammatory mediators, ROS and oxidative stress in gastric ulcer. The increase in the ROS levels causes that the pro-inflammatory mediators also increase [29]. GSH acts as a free radical scavenger and lipid peroxidation inhibitor, and joins the detoxification of the hydrogen peroxide together with various glutathione peroxidases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, such effects of RAS inhibitors are well recognized. 12,13) Second, in both studies, baseline covariates including risk factors, blood pressure, and plasma total cholesterol and fasting blood glucose levels were adjusted between the control and each treatment group.…”
Section: Discussionmentioning
confidence: 99%